Early Blight Infection and the Influence of Biocontrol Agents on Three Wild Potato Relatives : Implications for Integrated Pest Management (IPM) in Potato - Lankinen, Åsa; Andersen, Christian B.; Mostafanezhad, Hadis; De Pasqual, Chiara; Hederström, Veronica; Stridh, Linnea J.; Liljeroth, Erland; Grenville-Briggs, Laura (Potato Research, 2025)
Integrated pest management (IPM) is an important tool for sustainable crop production. IPM includes a diversity of methods, e.g., the use of biological control agents (BCAs) for disease control or growth promotion. While there is an increasing interest in the use of BCAs, less is known about their environmental costs and benefits on wild species, such as wild crop relatives. For example, a BCA may have the positive effect of controlling disease in wild relatives, but could also have the negative effect of growth promotion on wild relatives that act as weeds. In this study, we investigated if three wild potato relatives—the perennial climber Solanum dulcamara, and the annual weeds S. nigrum and S. physalifolium—could be infected by Alternaria solani, the causal agent of early potato blight in Sweden, and studied how two BCAs, Pythium oligandrum (a laboratory strain) and Bacillus amyloliquefaciens (Serenade), affected the disease and growth promotion in a series of greenhouse and field experiments. Our studies confirmed the semantic knowledge that A. solani can infect all three wild species, in particular the two annual species often growing as weeds in potato fields. We also found a disease-controlling effect of B. amyloliquefaciens, but not P. oligandrum, in the greenhouse. Some growth effects were found for both BCAs, but whether these were positive or negative varied with trait, plant species, and genotype. In conclusion, BCAs can confer both environmental costs and benefits on the three wild relatives of potato investigated in the current study, which should be taken into consideration for development of sustainable potato cultivation.
Keywords: Alternaria solani; Bacillus amyloliquefaciens; Disease epidemiology; Growth promotion; Pythium oligandrum; Wild Solanum species